Remating and Sperm Competition in Replicate Populations of Drosophila melanogaster Adapted to Alternative Environments - Arbuthnott, Devin (Public Library of Science, 2014)
The prevalence of sexual conflict in nature, as well as the supposedly arbitrary direction of the resulting coevolutionary trajectories, suggests that it may be an important driver of phenotypic divergence even in a constant environment. However, natural selection has long been central to the operation of sexual conflict within populations and may therefore constrain or otherwise direct divergence among populations. Ecological context may therefore matter with respect to the diversification of traits involved in sexual conflict, and if natural selection is sufficiently strong, such traits may evolve in correlation with environment, generating a pattern of ecologically-dependent parallel evolution. In this study we assess among-population divergence both within and between environments for several traits involved in sexual conflict. Using eight replicate populations of Drosophila melanogaster from a long-term evolution experiment, we measured remating rates and subsequent offspring production of females when housed with two separate males in sequence. We found no evidence of any variation in male reproductive traits (offense or defense). However, the propensity of females to remate diverged significantly among the eight populations with no evidence of any environmental effect, consistent with sexual conflict promoting diversification even in the absence of ecological differences. On the other hand, females adapted to one environment (ethanol) tended to produce a higher proportion of offspring sired by their first mate as compared to those adapted to the other (cadmium) environment, suggesting ecologically-based divergence of this conflict phenotype. Because we find evidence for both stochastic population divergence operating outside of an ecological context and environment-dependent divergence of traits under sexual conflict, the interaction of these two processes is an important topic for future work.